Correction: Killer whale respiration rates. - Tess M McRae; Beth L Volpov; Evan Sidrow; Sarah M E Fortune; Marie Auger-Méthé; Nancy Heckman; Andrew W Trites (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0302758.].